1984
DOI: 10.1002/star.19840360408
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Cyclodextrin by Aspergillus oryzae α‐Amylase

Abstract: The hydrolysis of α‐, β‐ and γ‐cyclodextrins by Aspergillus oryzae α‐amylase was studied at pH 5.2 and 37°C. The kinetic parameters were determined and it was found that the V max value increased markedly in the order α‐, β‐ and γ‐cyclodextrin, but no significant difference was observed in the Km values. The qualitative and quantitative distribution of the hydrolysis products were determined by HPLC. In the case of γ‐cyclodextrin the time course of the kinetic parameters was compared to the qualitative and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Considering that α-amylase is capable of hydrolyzing CDs 47, we also investigated the stability of OCD NP in aqueous solution of α-amylase. It was found that OCD NP was relatively stable for at least 24 h in the presence of α-amylase ( Figure S4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Considering that α-amylase is capable of hydrolyzing CDs 47, we also investigated the stability of OCD NP in aqueous solution of α-amylase. It was found that OCD NP was relatively stable for at least 24 h in the presence of α-amylase ( Figure S4A ).…”
Section: Resultsmentioning
confidence: 99%
“…39). Additionally, the enzymatic reaction of the γ-CDs was found to be a self-regulated system, i.e., the products (maltooligomers, glucose, maltose) of the enzymatic reaction worked as feedback for the hydrolysis rate of the γ-CDs 55 , resulting in increased lifetimes after each cycle ( Fig. 5c, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrolysis of a-, b-and c-cyclodextrins by Aspergillus oryzae a-amylase was studied at pH 5.2 and 37°C. The kinetic parameters were determined and while the V max value increased markedly in the order a-, b-and c-cyclodextrin the K m values did not show significant difference [9]. Some flexibility of c-cyclodextrin ring makes it susceptible for opening by amylases.…”
Section: Introductionmentioning
confidence: 99%
“…The active center of amylase enzymes has several subsites and the reaction speed depends on the length of the malto-oligomer [9,10]. This reaction was studied in details by Kandra et al [11][12][13] and a computer program was developed to determine the binding energy of the subsites of active center [14].…”
Section: Introductionmentioning
confidence: 99%